Keabsahan Tindakan Gubernur Maluku Menunjuk PT Bumi Perkasa Timur Sebagai Mitra Kerja Sama Pemenfaatan Ruko Dikawasan Mardika - Salhuteru, James Ricardo; Salmon, Hendrik; Pattinasarany, Johanes (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Based on Regional Regulation No. 9 of 2017 stipulates that the determination of cooperation partners for the utilization of regional property is carried out through a tender, not a direct appointment by the Governor. However, the Governor of Maluku made the direct appointment of PT. Bumi Perkasa Timur as a cooperation partner for the use of shophouses in the Mardika area as regional property.Purposes of the Research: To analyze the legitimacy of the actions of the Governor of Maluku, he appointed PT BUMI PERKASA TIMUR as a Cooperation Partner for the Utilization of Shophouses in the Mardika Area as regional property. To analyze the legal consequences of the actions of the Governor of Maluku, he appointed PT BUMI PERKASA TIMUR as a Cooperation Partner for the Utilization of Shophouses in the Mardika Area as regional property.Methods of the Research: This research uses normative juridical research methods. The research approach used by the author is a statutory approach (Statute Approach) and a conceptual approach (Conceptual Approach). The procedure for collecting legal materials is carried out by means of library research. The legal materials used by the author in this study are primary legal materials, secondary legal materials, and tertiary legal materials.Results of the Research: The actions of the Governor of Maluku made the appointment of PT. Bumi Perkasa Timur as a cooperative partner in the use of shophouses in the Mardika area is an action that has no validity, because it is not in accordance with the established procedures.